Ultrahigh-intensity laser-produced plasmas as a compact heavy ion injection source - Krushelnick, K; Clark, E; Allott, R; Beg, F; Danson, C; Machacek, A; Malka, V; Najmudin, Z; Neely, D; Norreys, P; Salvati, MR; Santala, M; et al. (IEEE, 2000)
The possibility of using high-intensity laser-produced plasmas as a source of energetic ions for heavy ion accelerators is addressed. Experiments have shown that neon ions greater than 6 MeV can be produced from gas jet plasmas, and well-collimated proton beams greater than 20 MeV have been produced from high-intensity laser solid interactions. The proton beams from the back of thin targets appear to be more collimated and reproducible than are high-energy ions generated in the ablated plasma at the front of the target and may be more suitable for ion injection applications. Lead ions have been produced at energies up to 430 MeV.